Pancreaticoduodenectomy for adenocarcinoma of the pancreatic head is justified in elderly patients: A Retrospective Cohort Study. (April 2016) - Renz, Bernhard W.; Khalil, Philippe N.; Mikhailov, Michael; Graf, Sandra; Schiergens, Tobias S.; Niess, Hanno; Boeck, Stefan; Heinemann, Volker; Hartwig, Werner; Werner, Jens; Bruns, Christiane J.; Kleespies, Axel
Abstract: Background: The increasing elderly population is an inevitable trend worldwide in developed countries. Therefore, we aimed to assess the experience of a tertiary pancreatic center with a very homogenous population comprising only patients diagnosed with PDAC of the pancreatic head in patients older than 75 years of age compared to their younger counterparts regarding the benefit in life expectancy and tumor biological aggressiveness. Methods: 300 patients underwent partial pancreaticoduodenectomy (PD) or pylorus preserving pancreaticoduodenectomy (PPPD) for PDAC of the pancreatic head between 2002 and 2012 and were evaluated with regard to their co-morbidities, clinicopathological and perioperative variables, postoperative morbidity, mortality and long term survival. Therefore, two groups according to the age at the procedure (A: <75 years, n = 241, B: ≥75 years, n = 59) were designed. Results: There were no differences between groups with regard to gender, performed procedure (PPPD or PD), operation time, blood loss, tumor invasiveness and grade of tumor differentiation, R-status, lymph node ratio, 30-day mortality, length of stay and adjuvant chemotherapy. Extended resections including total pancreatectomy were slightly more often performed in younger patients ( p  = 0.071) and trended toward a higher rate of surgical complications in patients <75 years of age ( p  = 0.183). A higher rate of preoperative co-morbidities in elderly patients (group B), was associated with more postoperative non-surgical complications ( p  = 0.002) in this group of patients. However, the median overall survival (19.2 vs. 18.4 months) did not differ significantly between groups. Conclusions: Major pancreatic surgery for ductal adenocarcinoma of the pancreatic head is justified in elderly patients. With careful patients' selection and prudent perioperative management, elderly patients will have a similar long term outcome despite the higher rate of postoperative morbidity based on non-surgical complications. Highlights: Major pancreatic surgery for PDAC of the pancreatic head is justified in elderly patients. With careful patients' selection and prudent perioperative management, elderly patients will have a similar long term outcome. Higher rate of postoperative morbidity based on non-surgical complications in elderly patients.